Covariance control for discrete-time stochastic switched linear systems. Issue 25 (2022) - Fiacchini, Mirko; Alamo, Teodoro
Abstract: This paper deals with the covariance control for discrete-time linear switched systems affected by additive stochastic noises. Given any periodic stabilizing switching law for the deterministic system associated to the stochastic one, a finite set of matrices is characterized that is an attractor for the system state covariance matrix sequence. Moreover, upper and lower bounds on the covariance matrices of the state are determined by the trajectories of one-dimensional linear systems.